Islamic Values-Based Learning Organization Model for Improving Madrasah Quality - Agus Jamaluddin; Iman Subasman; Muhamad Al Chudlori (MASI Mandiri Edukasi, 2026)
This study addresses the challenge of improving madrasah quality amid rapid educational transformation, in which many institutions still rely on bureaucratic, routine-based management practices that limit innovation and institutional learning. The objective of this research is to develop and analyze an Islamic values-based learning organization model as a strategic framework for sustainably enhancing the quality of madrasahs. The study employed a qualitative case study approach conducted in three State Islamic Senior High Schools (MAN) in Majalengka Regency. Data were collected through in-depth interviews, participant observation, and document analysis involving principals, teachers, administrative staff, and students. The data were analyzed thematically to identify patterns of organizational transformation and quality improvement. The findings reveal that the implementation of the model led to measurable improvements in four key areas: (1) increased teacher professionalism through collaborative and reflective learning practices, (2) transformation of instructional methods toward participatory and technology-supported learning, (3) strengthening of Islamic-based organizational culture characterized by shared values such as taqwa, ikhlas, and amanah, and (4) enhanced institutional autonomy through participatory and ethical leadership. The integration of learning organization principles with Islamic values functioned not merely as normative guidance but as operational mechanisms driving continuous improvement. This study concludes that an Islamic values-based learning organization model provides a holistic, context-sensitive framework that promotes both academic excellence and character development in madrasahs.